Implementation of the Government Internal Control System in Accounting and Financial Reporting Practices: A Case Study at the Southeast Pontianak Sub-District Office - Ria Nursani Putri Kalimantari; Syarbini Ikhsan; Haryono Haryono; Rusliyawati Rusliyawati; Juanda Astarani (Poltanesa, 2025)
In an effort to strengthen good governance, the Government Internal Control System (SPIP) is a strategic instrument to improve accountability, transparency, and efficiency in the public sector. This study aims to explore the implementation of SPIP in the Southeast Pontianak Sub-district Office, identify the challenges faced, and understand the factors that affect its effectiveness. Using a qualitative approach with a case study method, data was collected through in-depth interviews, participant observations, and document analysis. The research informants were selected purposively from the structural ranks and technical staff of the sub-district. The results of the study show that the implementation of SPIP is still administrative and has not been fully integrated in financial management practices and public services. The five elements of SPIP the control environment, risk assessment, control activities, information and communication, and monitoring have not been carried out systematically. The main challenges include low understanding and competence of human resources, lack of leadership commitment, limited supporting infrastructure, weak technical regulations at the sub-district level, and ineffective evaluation mechanisms. Employee perceptions of SPIP also show that there is a gap between policies and practices in the field. In conclusion, the implementation of SPIP at the Southeast Pontianak Sub-district Office is still not optimal and requires comprehensive interventions, including strengthening human resource capacity, improving proactive leadership, and integrating SPIP into a more adaptive and participatory government management system. The results of this study are expected to be the basis for improving SPIP implementation policies at the local level.